Sex-specific response to whole-body vibration training: a randomized controlled trial - Hartard, Manfred; Seiler, Aaron; Spitzenpfeil, Peter; Engel, Linus; Hartard, Diana; Amine Fenneni, Mohamed; Ben Saad, Helmi (Biology of Sport, 2022)
A few studies have indicated that males and females respond differently to whole-body vibration (WBV) training. However, the existing insights are still insufficient and they cannot be transferred to sex-specific practice planning. To evaluate the effect of 5-week WBV training on neuromuscular [countermovement jump (CMJ), squat jump (SJ)] and cardiovascular [heart rate and blood pressure] data, taking into account sex-specific effects. This is a comparative experimental study including 96 healthy adults, divided into two groups: a WBV group (25 females and 24 males) and a control group (27 females and 20 males). The participants attended nine to ten training sessions (twice a week for 5 weeks), each lasting approximately 30 min. Both groups performed the same exercise routine on the vibration training device. For the WBV group, the training device was vibrating during the whole training session, including the breaks. For the control group, it was turned off. Maximum jump height (H, cm) and maximum relative power (MRP, kW/kg) were noted during CMJ and SJ performed on a force plate. Resting (sitting) heart rate (bpm) and blood pressure (mmHg) were measured twice, before and after the intervention. For each parameter, ∆data (= before – after) was calculated. Interactive effects of sex (2) vs group (2) vs session (2) were noted only in males and they only concerned ∆SJMPR and ∆CMJH: compared to the control group, the WBV group had better ∆SJMPR (1.39 ± 3.05 vs -2.69 ± 4.49 kW/kg, respectively) and ∆CMJH (0.50 ± 6.14 vs -4.42 ± 5.80 cm, respectively). No sex-specific effect of WBV on neuromuscular (CMJ and SJ) or cardiovascular (heart rate and blood pressure) data was found.